2007
DOI: 10.2119/2006-00061.yao
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Tyroserleutide (YSL) on the Invasion and Adhesion of the Mouse Melanoma Cell

Abstract: Tyroserleutide (YSL) is an active, low-molecular-weight polypeptide, comprised of three amino acids, that has shown antitumor effects on human hepatocarcinoma BEL-7402 in vitro and in vivo. In this study, we evaluated the inhibition of YSL on invasion and adhesion of the mouse B16-F10 melanoma cell line by injecting B16-F10 cells into the tail veins of C57BL/6 mice to establish an experimental lung metastasis model. YSL inhibited B16-F10 cell metastasis to lung, reducing the number and area of metastasis lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
0
7
0
4
Order By: Relevance
“…Specifically, the B16F10 line has been shown to metastasize to the lungs when injected into the lateral tail vein and the majority of cells find themselves in the pulmonary tissue, but some are also localized in other organs [39] and is accepted as useful model for the study of lung metastasis [40,41]. Several other research studies stated the establishment of the experimental lung metastasis model or pulmonary metastatic model by intravenously injected mouse melanoma B16F10 in C57BL/6 mice [35,42,43]. Once B16F10 cells form tumor nodules in the lungs, they in turn promote lung fibrosis and collagen deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the B16F10 line has been shown to metastasize to the lungs when injected into the lateral tail vein and the majority of cells find themselves in the pulmonary tissue, but some are also localized in other organs [39] and is accepted as useful model for the study of lung metastasis [40,41]. Several other research studies stated the establishment of the experimental lung metastasis model or pulmonary metastatic model by intravenously injected mouse melanoma B16F10 in C57BL/6 mice [35,42,43]. Once B16F10 cells form tumor nodules in the lungs, they in turn promote lung fibrosis and collagen deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the growth and progression of most solid cancers are adhesion-and angiogenesis-dependent [34,35]. It has been reported that the degree of malignancy is directly proportional to the expression of ICAM-1 and VCAM-1 [36,37]. Both molecules are associated with melanoma progression and with an increased risk of the development of metastases.…”
Section: Discussionmentioning
confidence: 99%
“…We preferably focused on the low molecular weight polysaccharides, based on the previous reports on their favorable properties including better solubility, spatial stability, less toxicity, easier accessibility modifications and consequently increased anti-tumor activity compared to those with high molecular weight (Bittoun et al, 1999;Kimura et al, 2006;Yao et al, 2007;Zhou et al, 2005). In the current study, we evaluated some low molecular weight derivatives isolated from AbM and identified the most potent one, LMPAB.…”
Section: Discussionmentioning
confidence: 99%